2017
DOI: 10.1101/177345
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Epstein-Barr virus episome maneuvers between nuclear chromatin compartments during reactivation

Abstract: The human genome is structurally organized in three---dimensional space to facilitate functional partitioning of transcription. We learned that the latent episome of the human Epstein---Barr virus (EBV) preferentially associates with gene---poor chromosomes and avoids gene---rich chromosomes. Kaposi's sarcoma---associated herpesvirus behaves similarly, but human papillomavirus does not. Contacts localize on the EBV side to OriP, the latent origin of replication. This genetic element, and the EBNA1 protein that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…1a and Supplementary Table 2, 3). We identified numerous EBV 4C peaks throughout chromosomes with 10 kb resolution indicating that EBV tethering sites can be identified at the gene level and at higher resolution than previous studies 48 . The overall pattern of EBV 4C peaks from 5 baits revealed common peaks at specific genomic regions and a general distribution of peaks throughout all chromosomes.…”
Section: Resultsmentioning
confidence: 46%
See 1 more Smart Citation
“…1a and Supplementary Table 2, 3). We identified numerous EBV 4C peaks throughout chromosomes with 10 kb resolution indicating that EBV tethering sites can be identified at the gene level and at higher resolution than previous studies 48 . The overall pattern of EBV 4C peaks from 5 baits revealed common peaks at specific genomic regions and a general distribution of peaks throughout all chromosomes.…”
Section: Resultsmentioning
confidence: 46%
“…A recent study using Hi-C methods examined EBV interactions with host chromosome in various cell types 48 . In this study, EBV was found to associate with gene poor, AT-rich locations restricted to a subset of chromosomes through an EBNA1 independent, but OriP-dependent mechanism 48 . There are several technical differences in this Hi-C study compared to ours.…”
Section: Discussionmentioning
confidence: 99%
“…The EBV interactome has also been characterized using in-situ Hi-C assays, which generate chromosome conformation maps that provide a snapshot of how every restriction enzyme site associates with every other site throughout the genome. These studies showed that the latent EBV episome associates with gene poor regions, but relocalizes to gene-rich regions of the genome upon reactivation ( Moquin et al, 2017 ). While highly informative, these studies did not have the resolving power of the assays described here for MVM.…”
Section: Discussionmentioning
confidence: 99%
“…For example, BMRF1 induces centrosome amplification and chromosome instability in B cells in vitro and in vivo in a mouse model [ 118 ]. BGLF4 directly or indirectly induces DNA damage by retarding cellular S-phase progression or inducing premature chromosome condensation associated with a high risk of chromosomal breaks at common fragile sites [ 119 , 120 , 121 ]. EBV DNase was also found to induce GI in human epithelial cells through DNA damage induction and DNA repair repression [ 122 ].…”
Section: Ebv-related Diseases and Oncogenic Properties Of Zebramentioning
confidence: 99%